A graph-based modelling methodology for high-pressure networks applied on waterjet machining. (November 2018) - Niederberger, S.; Orjuela, R.; Schleuniger, P.; Anderegg, R.; Basset, M.
Abstract: This paper proposes a graph-based methodology that models high-pressure networks of various topologies. Therefore, a mathematical modelling of a supply network for waterjet machining will be introduced. High-pressure components are assigned to homogeneous segments, each representing a local pressure state as a differential equation. Segments are subsequently interconnected along the fluid flow path as an algebraic equation that allocates a fluid flow to the interconnections, resulting in a lumped parameter model. For this purpose, a graph network description has been used to approximate the spatially distributed high-pressure system. In this way, the proposed methodology offers a flexible modelling to cope with different network topologies. Moreover, a variable fluid compressibility has also been introduced so that a wide operating range can be included. This modelling methodology has been applied to a supply network for waterjet machining. The resulting mathematical model has been verified by measurements from a test bench with a pressure range of 100−400 MPa. It was shown that a variable fluid compressibility improves the model's accuracy and that modelling errors can be reduced in comparison to other existing methodologies.